JURIDICIAL REVIEW OF LIMITATION OF MARRIAGE AGENCY BASED ON LAW NO 16 OF 2019 ABOUT MARRIAGE - Fatimah HS; Hambali thalib; Zainuddin (Meraja journal, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal